The Inevitability of "Standard" English: Discursive Constructions of Standard Language Ideologies. (April 2016) - Davila, Bethany
Although standard language ideologies have been well researched and theorized, the practices that lead to the reproduction and enactment of these ideologies deserve attention. Specifically, there remains a need to study language that both reveals reliance on standard language ideologies and perpetuates these ideologies within the field of writing studies, undermining the field's efforts to challenge standard English's ongoing privileged position. This article examines the role of language in perpetuating perceptions of standard English as linguistically neutral regardless of personal or field-wide views about linguistic equality and the value of linguistic diversity. Specifically, I describe the discursive practices of standard language ideologies—what I term standard language discourse—that allow for a positioning of standard English as normal, natural, non-interfering, and widely accessible. Finally, I explore how to resist or challenge this positioning.